Identifying sources of social capital among the farmers of the rural Sindh Province of Pakistan - Sheikh, Muhammad Javed; Redzuan, Ma'rof; Abu Samah, Asnarulkhadi; Ahmad, Nobaya (Czech Academy of Agricultural Sciences, 2015)
Social capital is the spirit of social relations. While it contains social resources, and is interrelated with other forms of capitals, there are some delusions among the scholars over its generation. The study was conducted to identify the factors possibly involved in the fluctuation of social capital, in which the structural social capital, bonding social capital and linking social capital of the water-user associations were measured, and it was linked to various socioeconomic, demographic and farm characteristics of farmers. The multiple linear regression analysis revealed that the social capital was significantly influenced by the canal water availability, age, the drainage system availability, land holding, the farming experience and the family size. Furthermore, the canal water availability was found the most dominant indicator in relation to social capital to make it dynamic, in the rural Sindh province of Pakistan.